2019
DOI: 10.1128/jvi.00505-19
|View full text |Cite
|
Sign up to set email alerts
|

Progeny Varicella-Zoster Virus Capsids Exit the Nucleus but Never Undergo Secondary Envelopment during Autophagic Flux Inhibition by Bafilomycin A1

Abstract: Varicella-zoster virus (VZV) is an alphaherpesvirus that lacks the herpesviral neurovirulence protein ICP34.5. The underlying hypothesis of this project was that inhibitors of autophagy reduce VZV infectivity. We selected the vacuolar proton ATPase inhibitor bafilomycin A1 for analysis because of its well-known antiautophagy property of impeding acidification during the late stage of autophagic flux. We documented that bafilomycin treatment from 48 to 72 h postinfection lowered VZV titers substantially (P ≤ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…At this point, we reexamined our large archive of electron micrographs from past experiments and confirmed that even one or two naked capsids within a single micrograph were very difficult to find in the cytoplasm of VZV-infected MRC-5 or human melanoma cells (29). Further, we noted in our prior paper that naked capsids were sometimes in the cytoplasm of BAF-treated MRC-5 cells, often surrounding but not within vacuolar compartments (8). However, the number was fewer than that seen in VZV-infected Pompe cells.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…At this point, we reexamined our large archive of electron micrographs from past experiments and confirmed that even one or two naked capsids within a single micrograph were very difficult to find in the cytoplasm of VZV-infected MRC-5 or human melanoma cells (29). Further, we noted in our prior paper that naked capsids were sometimes in the cytoplasm of BAF-treated MRC-5 cells, often surrounding but not within vacuolar compartments (8). However, the number was fewer than that seen in VZV-infected Pompe cells.…”
Section: Resultssupporting
confidence: 55%
“…In one set of experiments, we examined VZV-infected cells by electron microscopy at early time points of 15 min, 8 h, 20 h, and 30 h after infection to document the minimal presence of inoculum virus. Therefore, we have an archive of over 1,000 electron micrographs, some on photographic paper and, more recently, in digital format (8). For this new research project, we observed an additional 483 digital electron micrographs of VZV-infected cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations